Asymmetric Lateral Ventricles—A Tale of Two Cases - Pahwa, Nakul (Indian Journal of Neurotrauma, 2021)
Asymmetry of the lateral ventricles is not an uncommon finding. On one end, it is a predictor of intracranial pathology, and on the other, it can represent a normal variant. It needs to be appropriately investigated. In this case report, we presented two cases of asymmetric lateral ventricles, their presentation, progression and management.
Keywords: asymmetry; lateral ventricles; asymmetry of the lateral ventricles